Analysis of the export market of the municipality of Altamira in the period of 2017-2018 - Santo, Welliton Jhon dos Santos do Espirito; de Lima, Luís Fernando Branco; Souza, Julia de Nazareth; de Oliveira, Amanda Fernandes; Ferreira, Matheus Monteiro; Pena, Heriberto Wagner Amanajás; Lisbôa, Educélio Gaspar; Chaves, Marcelo Santos (Seven Editora, 2023)
This article discusses the relevant theoretical perspectives about the city of Altamira-PA regarding its development and also will present an analysis of its insertion in foreign trade in the period from 2017 to 2018. For this, the competitiveness matrix methodology will be adopted as an analytical tool for describing the main historical and economic characteristics of Altamira, as well as identifying its most important products and which factors have the greatest influence on its composition, with collected data from foreign trade sources such as the Ministry Industry, Foreign Trade and Services (MDIC) and COMEX STAT, have resulted in aggregate data expressing the reality of the export sector of Altamira County. All this can help in the elaboration of measures that would be better adapted for the economic development of Altamira. DOI: https://doi.org/10.56238/devopinterscie-011